Poverty reduction and economic structure: Comparative path analysis for Mozambique and Vietnam - Channing Arndt; Andres Garcia; Finn Tarp; James Thurlow (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
While economic growth generally reduces income poverty, there are pronounced differences in the strength of this relationship across countries. Typical explanations for this variation include measurement errors in growth-poverty accounting and countries' different compositions of economic growth. We explore the additional influence of economic structure in determining a country's growth-poverty relationship and performance. Using multiplier and structural path analysis, we compare the experiences of Mozambique and Vietnam - two countries with similar levels and compositions of economic growth but divergent poverty outcomes. We find that the structure of the Vietnamese economy more naturally lends itself to generating broad-based growth. A given agricultural demand expansion in Mozambique will, ceteris paribus, achieve much less rural income growth than in Vietnam. Inadequate education, trade and transport systems are found to be more severe structural constraints to poverty reduction in Mozambique than in Vietnam. Investing in these areas can significantly enhance the effectiveness of Mozambican growth to reduce poverty.
Keywords: O10; O58; C69; 330; poverty; multipliers; structural path analysis; Mozambique; Vietnam; Armut; Wirtschaftswachstum; Wirtschaftsstruktur; Multivariate Analyse; Mosambik; Vietnam